PENDIDIKAN KEWIRAUSAHAAN BAGI SISWA UNTUK MENINGKATKAN PERKEMBANGAN JIWA, LINGKUNGAN, BUDAYA PADA SMA HANGTUAH 1 SURABAYA - Sutanto, J.E.; Sitepu, Rismawati Br; Sembiring, Murpin Josua; Tambunan, Damelina; Soetedja, Venny (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
Tujuan dari pengabdian masyarakat ini adalah agar siswa kelas XII dan SMA dapat mengembangkan semangat, iklim, budaya, dan kegiatan kewirausahaan dengan mendidik dan mendorong terciptanya lulusan yang mandiri dan menjadi wirausaha melalui program kewirausahaan. Subyek pengabdian ini adalah siswa SMA Hang Tuah 1 Surabaya. Luaran dari pengabdian ini antara lain terwujudnya model pengembangan kewirausahaan yang efektif dalam mengembangkan semangat, iklim, budaya, dan aktivitas kewirausahaan mahasiswa, mulai dari pendidikan kewirausahaan, motivasi serta peragaan contoh kegiatan kewirausahaan dari kampus Universitas Ciputra Surabaya secara langsung. ditangani oleh mahasiswa Ciputra yang sedang mengerjakan proyek. Hasil pengabdian ini menunjang program kewirausahaan yang telah terjalin di SMA Hang Tuah 1 Sidoarjo. Luaran yang dihasilkan berupa keluaran dan bentuk Hak Intelektual Indonesia bagi Dosen dan Mahasiswa Universitas Ciputra, serta diberitakan di surat kabar Malang Posco Media. Abstract. The aim of this community service is for 12th-grade and high school students to develop the spirit, climate, culture, and entrepreneurial activities by educating and encouraging the creation of graduates who are independent and become entrepreneurs through entrepreneurship programs. The subjects of this service are students from Hang Tuah 1 High School Surabaya. The outputs of this ,service include the realization of an effective entrepreneurial development model in developing the spirit, climate, culture, and entrepreneurial activities of students, starting from entrepreneurial education, motivation and demonstrating examples of entrepreneurial activities from the Ciputra University Surabaya campus which are directly handled by Ciputra students who currently on project. The results of this service support the entrepreneurship program that has been established at Hang Tuah 1 Sidoarjo High School. The resulting output is in the form of output and the form of Indonesian Intellectual Rights for Ciputra University Lecturers and Students, and was covered in the Malang Posco Media newspaper. Keywords; Entrepreneurship education; Soul development; Environment; Culture